Effects of thymol and carvacrol, alone or in combination, on fermentation and microbial diversity during in vitro culture of bovine rumen microbes. Issue 3 (4th March 2019) - Castañeda-Correa, Alejandro; Corral-Luna, Agustin; Hume, Michael E.; Anderson, Robin C.; Ruiz-Barrera, Oscar; Castillo-Castillo, Yamicela; Rodriguez-Almeida, Felipe; Salinas-Chavira, Jaime; Arzola-Alvarez, Claudio
Abstract: Two essential oils (EO), thymol and carvacrol, were used in six ratio (100:00, 80:20, 60:40, 40:60, 20:80 and 00:100) combinations of both EO and in a dose of 0.2 g L −1 in bovine ruminal culture medium, 24-h cultures, to evaluate effects on total gas production (TGP), methane production, in vitro dry matter digestibility (IVDMD) and in vitro culture population dynamics of methanogenic and total bacteria. Total DNA extracted from ruminal microorganisms was subjected to denaturing gradient gel electrophoresis (DGGE)-polymerase chain reaction (PCR) to examine effects on bacterial populations. The effect of EO on TGP and IVDMD were assessed by comparison to untreated control cultures. In general, methane production by the microbial populations appeared to be higher with treatments containing the highest concentration of thymol than with treatments containing more carvacrol resulting in a tendency for greater methane-inhibiting activity achieved as the thymol concentration in the thymol:carvacrol mixtures decreased linearly. The population of total bacteria with a 74.5% Dice similarity coefficient for comparison of DGGE band patterns indicating shifts in bacterial constituents as EO ratios changed. No effects on TGP, IVDMD while only slight shifts in the methanogenic populations were seen with an overall 91.5% Dice similarity coefficient.